IMPLEMENTASI SISTEM PAKAR DALAM PENANGANAN PENYAKIT KANKER - M Adie Syaputra; Kurnia Wulan Suci (Sienna, 2021)
The use of information technology in patient health services in hospitals will never be separated to achieve efficiency and time effectiveness. In the health sector, the use of technology is still very much needed, let alone its use. In the treatment of cancer, many efforts have been made by patients from prevention, screening (early detection), diagnosis, and treatment. With expert methods are expected to help in providing recommendations in the treatment of cancer. The expert system will read the inputted symptoms to be able to make recommendations in dealing with cancer. The OMT method is an object-based approach methodology that uses use case tools in building software.